Community Empowerment in Onion Waste Management Programs to Create A Circular Economy - Nina Ari Wahyuni; Ahmadi Susilo; Nugrahini Susantinah Wishnujati (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: The purpose of this study is to get an overview of the application of circular economy to the community empowerment process carried out by PT Paiton Energy’s CSR in the Sumber Rejeki farmer group in managing low-quality onion waste as raw material for instant seasoning. Design/methodology/approach: The type of research is descriptive qualitative with a case study approach in the Sumber Rejeki farmer group, Pondok Kelor Village, Paiton District, Probolinggo Regency. Data were obtained through in-depth interviews, participatory observations and documentation. The subject of the study was a member of a fortune-source farmer group consisting of 10 people. Findings: The results of community empowerment activities have implemented a circular economy, farmer groups have been skilled in utilizing low-quality onion waste into ready-to-eat cooking seasonings and into processed products typical of the village and producing an economic value of Rp. 8,488,000.00 per harvest period. Thus efforts to save low-quality onion waste provide benefits in increasing the income of onion farmer groups. Research limitations/implications: Subjects in the study were limited to onion farmers who were members of the source farmer group and members who processed onion waste. Practical implications: This revenue will not be generated if the group does not carry out sewage treatment. Originality/value: The Sumber Rejeki Farmer Group is the first farmer group to process Onion waste and get a community empowerment program with a circular economy approach. Paper type: A case study